Sign learning of hearing children in inclusive day care centers—does iconicity matter? - Goppelt-Kunkel, Madlen; Stroh, Anna-Lena; Hänel-Faulhaber, Barbara (Frontiers in Psychology, 2023)
An increasing number of experimental studies suggest that signs and gestures can scaffold vocabulary learning for children with and without special educational needs and/or disabilities (SEND). However, little research has been done on the extent to which iconicity plays a role in sign learning, particularly in inclusive day care centers. This current study investigated the role of iconicity in the sign learning of 145 hearing children (2;1 to 6;3 years) from inclusive day care centers with educators who started using sign-supported speech after a training module. Children's sign use was assessed via a questionnaire completed by their educators. We found that older children were more likely to learn signs with a higher degree of iconicity, whereas the learning of signs by younger children was less affected by iconicity. Children with SEND did not benefit more from iconicity than children without SEND. These results suggest that whether iconicity plays a role in sign learning depends on the age of the children.